Efektivitas Media Poster Menggunakan Augmented Reality Pada Materi Proklamasi Kemerdekaan Indonesia Di SMA/MA - Saleh, Az Zhukruf Nadhillah; Hastuti, Hera (Jurnal Kronologi, 2025)
This research is motivated by the lack of IT-based learning media in schools. The learning process still centers on conventional teaching methods and rarely uses IT-based media. The purpose of this research is measure the effectiveness of poster media using augmented reality in high schools. This research is a continuation study. The model used in this research quantitative method. The data source used is the XI F class from MAN 1 Padang and the XI F 2 SMA N 16 Padang. This research was conducted in August 2024. Data collection was conducted through the distribution of questionnaires, interview, and documentation. Data analysis was carried out quantitatively using the mean. The research results show that the effectivaness of poster media using augmented reality, according to students, fall into the effective category with a percentage result of 85.12 %. The results of interview with eleven students from the two schools concluded that poster media using augmented reality is effective as a medium in history learning.